Appropriate Use of Antimicrobial Agents in Urinary Tract Infections: Perception of Physicians and Resident Doctors - Jitendra D. Lakhani; Sucheta J. Lakhani; Shah Meera; Panchasara Sanket; Jain Sandeep (Journal of Integrated Health Sciences)
Appropriate and rational use of antibiotics in common infection syndrome such as urinary tract infection (UTI) is the need of the day to prevent bacterial resistance and side effects. Various protocols and guidelines are available for its use; however, perception as well as practices of clinicians may play an important role in their implementations. Methodology: To find problems as well as dilemma in regard to “when,” “what,” and “how long” to use antibiotics in UTI, a questionnaire and opinion-based study was conducted. Sixty clinicians engaged in adult internal medicine practice in Gujarat participated in the study. Many of the participants were resident doctors engaged in serving patients in the outpatient department, teaching hospitals, and medical intensive care units. Results: UTI was the second most common condition where the use of antibiotics is warranted in their practice. All of them had dilemma in the use of antibiotics because of various reasons. Majority did not ask for urine culture examination before giving antibiotics in uncomplicated UTI, but they demanded it in cases of recurrent UTIs, hospitalized patients, and pregnant patients. Their practice was akin to guidelines as far as treatment for asymptomatic bacteriuria was concerned. Fluoroquinolones and beta-lactam antibiotics were the choice of antibiotics in uncomplicated UTIs when urine culture was not ordered and was satisfied with clinical cure. Beta-lactam antibiotics were the choice in pregnant women having UTIs. Fifty-six percent responses favored 5–7-day treatment, whereas 17.86% favored 3-day treatment with fluoroquinolones or beta-lactam antibiotics. Although they were conscious and vigilant about antibiotic resistance problems, limitations did exit in their management plan which bothered them. Conclusions: Gaining insight from perceptions, knowledge, and practices of clinicians regarding the use of antibiotics in common situations such as UTI may be necessary to formulate a plan for local protocol and strategy. Antibiotic stewardship is an essential step. Shortening duration of antibiotics and use of appropriate antibiotics in different clinical situations of UTI may help to prevent antibiotic resistance. This topic needs priority in medical and paramedical education curriculum.